Isolation and assessment of the molecular and electronic structures of azo-anion-radical complexes of chromium and molybdenum. Experimental and theoretical characterization of complete electron-transfer series. - Joy, S; Krämer, T; Paul, N; Banerjee, P; McGrady, J; Goswami, S (2011)
The reaction of 3 equiv of the ligand 2-[(2-chlorophenyl)azo]pyridine (L(a)) or 2-[(4-chlorophenyl)azo]pyridine (L(b)) with 1 equiv of Cr(CO)(6) or Mo(CO)(6) in boiling n-octane afforded [Cr(L(a/b))(3)](0) (1a and 1b) and [Mo(L(a/b))(3)](0) (2a and 2b). The chemical oxidation reaction of these neutral complexes with I(2) in CH(2)Cl(2) provided access to air-stable one-electron-oxidized species as their triiodide (I(3)(-)) salts. The electronic structures of chromium and molybdenum centers coordinated by the three redox noninnocent ligands L(a/b) along with their redox partners have been elucidated by using a host of physical methods: X-ray crystallography, magnetic susceptibility measurements, nuclear magnetic resonance, cyclic voltammetry, absorption spectroscopy, electron paramagnetic resonance spectroscopy, and density functional theory. The four representative complexes, 1a, [1a]I(3), 2a, and [2a]I(3), have been characterized by X-ray crystallography. The results indicate a predominant azo-anion-radical description of the ligands in the neutral chromium(III) species, [Cr(III)(L(•-))(3)], affording a singlet ground state through strong metal-ligand antiferromagnetic coupling. All of the electrochemical processes are ligand-based; i.e., the half-filled (t(2g))(3) set of the Cr(III) d(3) ion remains unchanged throughout. The description of the molybdenum analogue is less clear-cut because mixing between metal- and ligand-based orbitals is more significant. On the basis of variations in net spin densities and orbital compositions, we argue that the oxidation events are again primarily ligand-based, although the electron density at the molybdenum center is clearly more variable than that at the chromium center in the corresponding series [1a](+), 1a, and [1a](-).